Quality management - Customer satisfaction - Guidelines for business-to-consumer electronic commerce transactions - International Organization for Standardization
This International Standard provides guidance for planning, designing, developing, implementing, maintaining and improving an effective and efficient business-to-consumer electronic commerce transaction (B2C ECT) system within an organization. It is applicable to any organization engaged in, or planning to be engaged in, a business-to-consumer electronic commerce transaction, regardless of size, type and activity. This International Standard is not intended to form part of a consumer contract or to change any rights or obligations provided by applicable statutory and regulatory requirements. This International Standard aims to enable organizations to set up a fair, effective, efficient, transparent and secure B2C ECT system, in order to enhance consumers' confidence in B2C ECTs and increase the satisfaction of consumers. It is aimed at B2C ECTs concerning consumers as a sub-set of customers. The guidance given in this International Standard can complement an organization's quality management system.